If f(x) = 3x + 10 and g(x)


If $f(x)=3 x+10$ and $g(x)=x^{2}-1$, then $(f \circ g)^{-1}$ is equal to


$f o g(x)=f(g(x))$



$=3 x^{2}-3+10$

$=3 x^{2}+7$

Thus, $\operatorname{fog}(x)=3 x^{2}+7$

$\Rightarrow y=3 x^{2}+7$

$\Rightarrow 3 x^{2}=y-7$

$\Rightarrow x^{2}=\frac{y-7}{3}$

$\Rightarrow x=\pm \sqrt{\frac{y-7}{3}}$

$f o g^{-1}(x)=\pm \sqrt{\frac{x-7}{3}}$

Hence, $(\text { fog })^{-1}$ is equal to $\pm \sqrt{\frac{x-7}{3}}$.

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now